Urhobo-English Loanwords Coda Adaptation: A Constraint-Based Account - Philip Oghenesuowho Ekiugbo; Cecilia Amaoge Eme (Journal of Linguistics and Language Teaching)
This study examines how codas of Urhobo-English loanwords are adapted and shows that the strategies adopted in repairing loanword coda in Urhobo are driven by syllabification constraints and universal conventions. Syllabification conditions in languages that forbid filled coda will require that all the consonant sounds in a phonological word that are to be found in the phonetic string are parsed as onsets. Assuming this is true, it has implications for loanword adaptation. Urhobo exclusively permits the open syllable type. Implicitly, all the coda elements of loanwords are likely to be licensed as onsets, which may result in a possible ‘illicit’ onset cluster given the onset condition requirement of the language. Accordingly, this study examines the attested patterns of adaptation of English coda in Urhobo loanwords and their motivations as well as implications. The discussion is built around the theory of constraints and repair strategies.